Effective directors: The right questions to ask (QTA) - Charlotte Valeur; Claire Fargeot (Routledge, 2022)
"Being a good board member is not about knowing everything; it is about asking the right questions and challenging appropriately. Effective Directors: Questions To Ask (QTA) is a reference book for board members and executives globally to support them in their work. With chapters written by senior company board members and respected figures in corporate governance, the questions have been drawn together to offer food for thought and useful prompts that take Boards beyond operational discussions. The book clearly presents the key areas to be considered by the Board (there are over 50 in total) and range from Board composition, to data security, diversity and inclusion, and succession planning. The questions are ones that boards, in any organisation, should be asking themselves, their fellow board members, service providers, executives and other stakeholders to ensure that the right issues are raised, transparency and effective oversight are achieved, and the Board is fulfilling its role in governing the organisation. In addition to being invaluable for board members, the book is also a very useful tool for executives in understanding the kind of questions their board members are likely to ask, and the kind of questions that should be asked and discussed in the boardroom"–
Keywords: 650; Boards; Corporate governance; Corporate social responsibility; Corporate strategy; CSR; Leadership; Organizational culture; Board of Directors; Corporate Governance